2014
DOI: 10.1016/j.nrl.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Tiempo de llegada hospitalaria y pronóstico funcional después de un infarto cerebral: resultados del estudio PREMIER

Abstract: A high percentage of patients had short hospital arrival times; however, less than 3% underwent thrombolysis. Although many factors were associated with early hospital arrival, it is a priority to identify in-hospital barriers to performing thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Studies utilized various methods for analyzing the effect of age. In short, being younger was associated both with early ( 63 , 83 , 96 ) and delayed ( 57 , 91 , 126 ) presentation, and similarly older patients were associated with both early ( 37 , 43 , 59 , 77 , 114 ) and delayed ( 56 , 57 , 62 , 74 , 83 , 121 ) presentation. There may be a lack of urgency in younger patients with stroke ( 152 ), and symptoms exhibited by older patients may be more readily interpreted as stroke and perceived as an emergency ( 43 ).…”
Section: Time To Hospital Arrival: Male Versus Female and Patient Agementioning
confidence: 91%
“…Studies utilized various methods for analyzing the effect of age. In short, being younger was associated both with early ( 63 , 83 , 96 ) and delayed ( 57 , 91 , 126 ) presentation, and similarly older patients were associated with both early ( 37 , 43 , 59 , 77 , 114 ) and delayed ( 56 , 57 , 62 , 74 , 83 , 121 ) presentation. There may be a lack of urgency in younger patients with stroke ( 152 ), and symptoms exhibited by older patients may be more readily interpreted as stroke and perceived as an emergency ( 43 ).…”
Section: Time To Hospital Arrival: Male Versus Female and Patient Agementioning
confidence: 91%
“…The purpose of establishing stroke centre is to improve stroke medical staff and facilities, so as to adapt them to the methods of stroke treatment and improve the level of stroke diagnosis and treatment. 7 The US health facility accreditation programme classifies stroke centres into three levels: CSC, PSC and stroke ready hospital. As early as 2000, BAC published a proposal to develop PSC, so as to improve the level of stroke diagnosis and treatment in the USA and improve stroke outcomes.…”
Section: Chapter 3: Regional Cooperative Network Construction Of Stromentioning
confidence: 99%
“…Previous studies showed that early hospital arrival was a significant factor for better functional outcomes [13][14][15]. However, patients who received reperfusion therapy during the acute phase were included in most of these studies; therefore, better outcomes of early arrivers might be owing to reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%